Stories of Identity among Black, Middle Class, Second Generation Caribbeans We, Too, Sing America - Lorick-Wilmot, Yndia S. (Springer International Publishing, 2018)
This volume addresses how black, middle class, second generation Caribbean immigrants are often overlooked in contemporary discussions of race, black economic mobility, and immigrant communities in the US. Based on rich ethnography, Yndia S. Lorick-Wilmot draws attention to this persisting invisibility by exploring this generation's experiences in challenging structures of oppression as adult children of post-1965 Caribbean immigrants and as an important part of the African-American middle class. She recounts compelling stories from participants regarding their identity performances in public and private spaces-including what it means to be "black and making it in America"-as well as the race, gender, and class constraints they face as part of a larger transnational community. .